An antibody to IL-1 receptor 7 protects mice from LPS-induced tissue and systemic inflammation - Jiang, Liqiong; Lunding, Lars P.; Webber, William S.; Beckmann, Karsten; Azam, Tania; Falkesgaard Højen, Jesper; Amo-Aparicio, Jesus; Dinarello, Alberto; Nguyen, Tom T.; Pessara, Ulrich; Parera, Daniel; Orlicky, David J.; et al. (Frontiers in Immunology, 2024)
Introduction Interleukin-18 (IL-18), a pro-inflammatory cytokine belonging to the IL-1 Family, is a key mediator ofautoinflammatory diseases associated with the development of macrophage activation syndrome (MAS).High levels of IL-18 correlate with MAS and COVID-19 severity and mortality, particularly in COVID-19patients with MAS. As an inflammation inducer, IL-18 binds its receptor IL-1 Receptor 5 (IL-1R5), leadingto the recruitment of the co-receptor, IL-1 Receptor 7 (IL-1R7). This heterotrimeric complex subsequentlyinitiates downstream signaling, resulting in local and systemic inflammation. Methods We reported earlier the development of a novel humanized monoclonal anti-human IL-1R7 antibody whichspecifically blocks the activity of human IL-18 and its inflammatory signaling in human cell and wholeblood cultures. In the current study, we further explored the strategy of blocking IL-1R7 inhyperinflammation in vivo using animal models. Results We first identified an anti-mouse IL-1R7 antibody that significantly suppressed mouse IL-18 andlipopolysaccharide (LPS)-induced IFNg production in mouse splenocyte and peritoneal cell cultures. Whenapplied in vivo, the antibody reduced Propionibacterium acnes and LPS-induced liver injury and protectedmice from tissue and systemic hyperinflammation. Importantly, anti-IL-1R7 significantly inhibited plasma,liver cell and spleen cell IFNg production. Also, anti-IL-1R7 downregulated plasma TNFa, IL-6, IL-1b,MIP-2 production and the production of the liver enzyme ALT. In parallel, anti-IL-1R7 suppressed LPSinducedinflammatory cell infiltration in lungs and inhibited the subsequent IFNg production andinflammation in mice when assessed using an acute lung injury model. Discussion Altogether, our data suggest that blocking IL-1R7 represents a potential therapeutic strategy to specificallymodulate IL-18-mediated hyperinflammation, warranting further investigation of its clinical application intreating IL-18-mediated diseases, including MAS and COVID-19.